HUBUNGAN PENGETAHUAN DAN POLA PENGASUHAN TERHADAP GIZI KURANG PADA BALITA USIA 12-59 BULAN - Harleli Harleli (NHM PRESS, 2022)
Toddlers are an age group that is vulnerable to nutrition, because children under five are in a transition period. Good nutritional support requires mother's knowledge in providing care for children. This study aims to determine the relationship between maternal nutritional knowledge, parenting patterns, feeding habits, and the incidence of malnutrition in children aged 12-59 months in the working area of ​​the Soropia Public Health Center. The design used in this study is a quantitative study with a cross sectional design where the dependent variables are measured simultaneously. The sampling technique used probability sampling with simple random sampling method. The sampling method to determine the nutritional status of children under five was carried out by weighing and measuring height. The research instrument used a knowledge and parenting questionnaire sheet. The analysis used is univariate and bivariate. The statistical test used is the Chi Square test. Univariate results showed that toddlers had good nutritional status 35.7%, mothers of toddlers had good nutrition knowledge, 77.1%, mothers of toddlers had good parenting patterns of 22.8% mothers of toddlers had good feeding habits, Bivariate analysis results showed variables of mother's knowledge (p-value = 0.445) and maternal parenting (p-value = 0.013). It can be concluded that mother's knowledge is not related to undernutrition status, while mother's upbringing has a relationship with undernutrition status. It is recommended to mothers to provide good parenting to their toddlers.